Risk Management for Building Construction Professionals - Gorecki, Jaroslaw, author; Yanqing, Huang, author; Deng, Liyan, author; Hamzah Abdul Rahman, author; Bizon-Gorecka, Jadwiga, author; Antunes, Ricardo, author; Chen, Wang, author; Gonzalez, Vicente, author; Nur Hamizah Ariffin, author; Ming, Li, author; Azadeh Sohrabinejad, author; Mehdi Rahimi, author; et al. (London : Auris Reference Limited, 2018)
Includes bibliographies and index